How to Teach English to Children Early on - Rizki Apriva Hidayana; Usman A. Yakubu (International Journal of Ethno-Sciences and Education Research, 2022)
Infrastructure and facilities should be sufficient to support the early introduction of English. To properly implement learning management, the teacher, who is a part of the learning process manager, must be aware of the early childhood thinking framework (AUD). Learning should be controlled to produce engaging and fulfilling learning activities. To make learning English for young children meaningful and enjoyable, singing (song) is used as a teaching tool. Children can be engaged in learning English by using a variety of approaches, tactics, games, and learning resources that will make them feel like they are playing rather than learning. Even the local culture can be useful for making learning enjoyable for AUD. The topic of learning English for AUD, in general, and through singing, in particular, will be covered in this article. A positive attitude toward learning English will keep AUD from being disinterested, dissatisfied, or even terrified by it.